Study of gene action and combining ability for seed yield and yield attributing traits in sunflower (Helianthus annuus L.): STUDY OF GENE ACTION AND COMBINING ABILITY FOR YIELD ATTRIBUTING TRAITS IN SUNFLOWER - S S LAKSHMAN; H P MEENA; N R CHAKRABARTY; M K GHODKE (Journal of Oilseeds Research, 2021)
Eight CMS lines and seven restorers were crossed in a line x tester fashion to elucidate the information on combining ability for achene yield, yield components and oil content and also to know the nature of gene action involved in inheritance ofimportant traits. A total of 56 crosses were evaluated for 9 different quantitative traits. The analysis of variance revealed the existence of a statistically significant difference between the genotypes used in crossing, which confirmed the differences among selected parents. Among the lines, CMS-853A and CMS-852A exhibited significant gca effect for most ofthe characters studied except autogamy (%) and were found to be the best combiners. Likewise, tester EC-601878 was the best combiner for plant height, head diameter, days to 50% flowering, achene yield, autogamy (%), hull content, volume weight and oil content. Twenty-three crosses showed significant positive sca effect for yield. Among the crosses, CMS-103A x EC-601978, CMS-10A x EC-601725, CMS-207AxEC-623023,P-89-1AxEC-623027, CMS-850AxEC-601878 andCMS-853AxEC-623027 exhibited higher positive sca effect for yield. Non additive component of the genetic variance was observed for majority of the traits studied.